A selection of parameters of tuned mass damper for multi-degree-of-freedom systems subjected to second order coloured noise excitation - Anh, Nguyen Dong; Sang, Nguyen Chi (Vietnam Journal of Mechanics, 2003)
Among the fundamental concepts for structure control, passive control systems have a significant role since they do not require additional energies produced by actuator. The basic of passive control is to incorporate a secondary system into the primary structure in order to transfer a part of the vibration energy of the primary system into the secondary one. In the paper the design of an optimal tuned mass damper (TMD) for a structure subjected to second order coloured noise excitation is investigated in order to minimize the sum of response mean squares of components of the primary system with a given ranking priority.